METABOLITES OF THE MICROBIOTA AS PSYCHIATRIC BIOMARKERS: SHORT-CHAIN FATTY ACIDS AND TRYPTOPHAN - Justyna Chudy; Łukasz Ćmok; Julia Dobrowolska; Jakub Robert Skalski; Gabriela Daniel; Karolina Halat; Antoni Hajdas; Natalia Kaczmarczyk; Iga Kałka; Julia Szmuc (International Journal of Innovative Technologies in Social Science, 2026)
Background: Severe psychiatric and neurodevelopmental disorders, including depression, bipolar disorder, and schizophrenia, remain a growing global health challenge, with diagnosis still largely based on subjective clinical assessment. Increasing evidence highlights the pivotal role of the microbiota–gut–brain axis (MGBA) in their pathophysiology, particularly neuroactive bacterial metabolites such as short-chain fatty acids (SCFA) and tryptophan derivatives (kynurenine and indole pathways). Aim: This review synthesizes current evidence on the clinical utility, diagnostic accuracy, and mechanistic relevance of SCFA and tryptophan metabolites as objective biomarkers in major psychiatric disorders. Methods: A structured literature review was conducted, focusing on multi-omics studies, randomized controlled trials, prospective cohorts, and high-quality meta-analyses. Molecular mechanisms involving GPCR and AhR signaling, HDAC inhibition, neuroinflammatory cascades, and blood–brain barrier regulation were examined. Diagnostic performance indicators, including AUC, sensitivity, and specificity, were analyzed. Results: SCFA and tryptophan metabolites critically regulate neurogenesis, BDNF expression, synaptic plasticity, microglial polarization, and immune homeostasis. Dysbiosis disrupts the balance between neuroprotective and neurotoxic kynurenine metabolites and reduces protective SCFA levels. Conclusion: Microbiota-derived metabolic signatures represent promising, objective tools for precision psychiatry. Integration of omics technologies with machine learning may enable biomarker-guided diagnosis and personalized therapeutic strategies targeting the gut–brain axis.